Monolateral external fixation for the progressive correction of neurological spastic knee flexion contracture in children - Carbonell, Pedro Gutiérrez (Springer Milan, 2007)
The purpose of this study was to report the results of the surgical treatment of spastic knee flexion contracture using tenotomy and progressive correction by external fixator–distractor devices. The study design involved a prospective observational study of 16 knees in nine patients with spastic flexion contracture greater than 30°. Treatment was indicated for both ambulatory and nonambulatory patients; and, in the latter group when sitting or personal hygiene was compromised. The average age was 11.6 years (range 10–17). Five of the patients were male and four female. There was one case of hemiplegia (11.1%), two cases of paraplegia (22.2%), and six cases of quadriplegia (66.7%). Six patients retained some walking capacity, while three had none. In all cases, distal lengthening of the hamstrings was carried out. A monolateral fixator with a gradual correction device was applied for a period of 4.8 weeks. The average follow-up was 26.6 months. The preoperative straight-leg raise was 55°. The popliteal angle was 58° preoperatively (range 30–80°), 8.5° on removal of the fixator, and 20° at the end of the follow-up. Complications: There were no superficial or deep infections, and no fractures or distal sensory–motor alterations. There was one case of arthrodiatasis of the knee (6.3%) which was resolved when the fixator was removed, and 11 cases of pin-track infection (68.7%) which were resolved with local care and oral antibiotics. To conclude, spastic knee flexion contracture can be treated gradually with monolateral external fixator with distraction devices, and with distraction modules which prevent acute stretching of the posterior neurovascular structures of the knee.